PENGEMBANGAN E-MODUL FISIKA BERBASIS MULTIREPRESENTASI PADA MATERI GERAK LURUS - Saputra, Bemie Eka; Pathoni, Haerul; Kurniawan, Dwi Agus (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2020)
The purpose of this development is to find out how to develop of the 3D electronic module pageflipp professional on straight motion material based on multiple representations. This type of research is research and development (R&D) research development using the ADDIE model. The subjects in this study were high school students in Class X at Muaro Jambi 11 High School. In this research development the questionnaire used was a closed questionnaire, in which the response was only asked to select the answers provided in the questionnaire. In this research development there are two questionnaires used, namely questionnaire for material experts (content), and perception questionnaire media for students. Qualitative data analysis is performed on the data collected, based on suggestions and comments from the validator. Quantitative data were obtained from the results of the distribution of questionnaires to students, with several alternative answer choices according to the Likert scale. The result of feasibility of the material expert validator were 86,67% with the very good category. The results of the feasibility of the media expert validator are 87% with the very good category. The results of students perceptions of the professional 3D pageflipp electronic module based on multirepresentation materials showed that 16 students responded very well and 14 students responded well.